Pan-Private Streaming Algorithms - Dwork, Cynthia; Naor, Moni; Pitassi, Toniann; Rothblum, Guy; Yekhanin, Sergey (Proceedings of The First Symposium on Innovations in Computer Science (ICS 2010), 2010)
Collectors of confidential data, such as governmental agencies, hospitals, or search engine providers, can be pressured to permit data to be used for purposes other than that for which they were collected. To support the data curators, we initiate a study of pan-private algorithms; roughly speaking, these algorithms retain their privacy properties even if their internal state becomes visible to an adversary. Our principal focus is on streaming algorithms, where each datum may be discarded immediately after processing.